PERANAN IBU DALAM KELUARGA SEBAGAI SUMBER INSPIRASI PENCIPTAAN KARYA SENI LUKIS - Muhammad Zulfi Khibron; Santoso Haryono (Texture:Art and Culture Journal, 2021)
The creation of this final project with the title The Role of Mothers in the Family as a source of inspiration for the creation of a painting was created to fulfill the requirements as an art scholar in the Indonesian Art Institute of Surakarta. mothers in educating children at this time, where there are facts faced by teenagers who deviate from existing norms. So that the negative impact of the behavior of teenagers is not widespread, then a mother must go directly to parenting children in shaping children's moral education. In the process of creating this final project through several stages, including the stages of idea creation, formulation of the concept of the creator and the realization of the work. The selected objects are human forms, puppets, dancers and other supporting objects. Processed according to the chosen style, namely figurative expressiveness, coloring using monochrome colors, namely black and white.